2003
DOI: 10.1002/adma.200305211
|View full text |Cite
|
Sign up to set email alerts
|

General Synthesis of Ordered Crystallized Metal Oxide Nanoarrays Replicated by Microwave‐Digested Mesoporous Silica

Abstract: sulated between any two points on the exposed area of two adjacent grids. Therefore, the transferred PPy lines are electrically separated and so might find application in plastic electronics. [19] In summary, we have demonstrated for the first time to our knowledge that electropolymerization on semiconductor substrates patterned with self-assembled films results in patternamplified conducting polymer microstructures. It is a facile and versatile way to directly form positively patterned threedimensional con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
253
1
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 430 publications
(264 citation statements)
references
References 51 publications
7
253
1
3
Order By: Relevance
“…have uniform mesocavities, high surface areas, and large pore volumes, which makes them the perfect candidates to serve as ''hard templates''. 35,37,38 Among these, SBA-16 has three-dimensional (3D) channels and a cubic Im3m (bodycentered cubic arrangement of cages with 8 apertures to the nearest neighbors) structure, which could be more favorable for mass and thermal transfer than a unidirectional pore system. 39 In order to introduce the maximum quantity of metal precursors, as many silanol groups as possible must be retained during the preparation of the silica template.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…have uniform mesocavities, high surface areas, and large pore volumes, which makes them the perfect candidates to serve as ''hard templates''. 35,37,38 Among these, SBA-16 has three-dimensional (3D) channels and a cubic Im3m (bodycentered cubic arrangement of cages with 8 apertures to the nearest neighbors) structure, which could be more favorable for mass and thermal transfer than a unidirectional pore system. 39 In order to introduce the maximum quantity of metal precursors, as many silanol groups as possible must be retained during the preparation of the silica template.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we found that the mesochannels of SBA-15 and KIT-6 were far from completely filled by metal precursors due to a large loss of Si-OH groups during the organic template removal process that involved a thermal calcination, 40,41 and this phenomenon has also been reported by other groups. 35,42,43 Other approaches such as using solvents and supercritical fluid extraction require long periods of operation (.24 h) and it is difficult to remove the organic template completely. 44 Tian et al proposed microwave irradiation as an effective technique for making organic templates such as Pluronic P123 quickly and with total removal of the onedimensional (1D) SBA-15 material with the greatest preservation of the original mesoporous structure and surface hydroxyl groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co3O4 nanostructures are expected to show even more excellent and tunable properties due to their versatile morphologies and structures. So far, many interesting nanostructures of Co3O4, including nanowires/nanorods [16,17], nanotubes [18,19], nanocubes [20][21][22], nanospheres [23][24][25], nanoplates [26] and nanowalls [27], have been prepared by using different growth methods. He et al synthesized Co3O4nanocrystals by a solubility controlled method using surfactant [28].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to calcination, MWD technique is facile and effective in removing the surfactant without sacrificing the silanols on pore walls and distinct framework shrinkage (90). It is reasonable that the microwave digested silicates with large pore volumes, high surface areas, and the most important of all, abundant silanols serve as the ideal hard templates for nanocasting replicas (90,91).…”
Section: ) Improving the Interaction Between Template And Precursormentioning
confidence: 99%